NALISIS PENGARUH CURRENT RATIO, FIRM SIZE, DAN ASSETS TANGIBILITY TERHADAP RETURN ON ASSET DENGAN DEBT TO TOTAL ASSET SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2008-2011) - NURSATYANI, ANISA; WAHYUDI, SUGENG; SYAICHU, MUHAMAD (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2014)
AbstractThis study to examine the effect of Current Ratio (CR), firm size, and assets tangibility to Return on Assets (ROA) with Debt to Total Assets (DTA) as an intervening variable. Object studies at mining companies listed on Indonesia Stock Exchange during 2008-2011. Sampling technique using purposive sampling method based on particular criteria which was appropriate with research purposes. This study use 15 mining companies. Methods of data analysis using multiple linear regression analysis, path analysis, and Sobel test.The results show Debt to Total Asset (DTA), Current Ratio (CR), and assets tangibility have negative effect on Return on Assets (ROA), but firm size has not effect on Return on Assets (ROA). Current Ratio (CR) has negative effect on Debt to Total Assets (DTA), but firm size and asset tangibility have not effect on Debt to Total Assets (DTA). Debt to Total Assets (DTA) is able to mediate relationship between Current Ratio (CR) to Return on Assets (ROA), but is not able to mediate relationship between firm size and assets tangibility to Return on Asset (ROA).